Physicochemical properties and plankton abundance in sanctuary and non sanctuary areas in the river Meghna, Bangladesh (Asian-Australasian Journal of Food Safety and Security, 2018)
The study was conducted in the selected sampling spots of sanctuary and non-sanctuary areas viz, Chor bhoirobi, Kaligonj, Ramgoti, Sureswar, Gajaria and upper area of Tarabunia to assess the impact of sanctuary on the abundance and biodiversity of fishes in the river Meghna from September 2015 to December 2015. Seven physicochemical parameters viz water temperature, air temperature, dissolve oxygen (DO), free carbon dioxide (Free CO2), pH, total alkalinity and total hardness, plankton community both phytoplankton and Zooplankton and CPUE with species composition of the river Meghna were studied. In the sanctuary area, Air temperature was found lowest 22.0°C ±1.1 in Ramgoti and highest 33.5°C±0.5 in Chor bhoirobi area of the river Meghna. Water temperature was found ranged from 20.8°C ±0.5 to 32.5°C ±0.2 in Kaligonj. Concentration of dissolve oxygen was found lowest 4.9± 0.1 mg/l in Ramgoti and highest in Chor bhoirobi 6.0±0.2 mg/l. Free carbon di oxide was found highest in Ramgoti 19±0.8 mg/l and lowest in Chor bhoirobi 13.4±0.4 mg/l. PH was found ranged from 7.2±0.6 in Kaligonj to 7.9±0.2 in Chor bhoirobi. Total alkalinity was found highest in Ramgoti 85±11.2 mg/l and lowest in Chor bhoirobi 72.7±4.7 mg/l. Total hardness was found highest in Ramgoti 150.0±45.1 mg/l and lowest in Kaligonj 52.0±12.7 mg/l. In the non sanctuary area, Air temperature was found ranged from 21.10°C ±1.0 to 33.2°C±0.8 in Gajaria and area of the river Meghna. Water temperature was found lowest 17.8°C ±1.3 in Gajaria and highest 31.2°C ±0.6 in Upper Tarabunia. Concentration of dissolve oxygen was found lowest 5.0± 0.3 mg/l in Gajaria and highest in Upper Tarabunia 5.9±0.1 mg/l. Free carbon di oxide was found highest in Gajaria 19.7±1.5 mg/l and lowest in Sureswar 16.2±0.7 mg/l. PH was found ranged from 7.3±0.6 in Sureswar to 7.9±0.2 in Gajaria. Total alkalinity was found ranged from 89.3±25 mg/l to 72.5±11.5 mg/l in Sureswar. Total hardness was found highest in Gajaria 89.2±14.9 mg/l and lowest in Sureswar 62.0±26.3 mg/l. Total 40 genera of phytoplankton belongs to Bacillariophyceae Chlorophyceae, Cyanophyceae, Dinophyceae, Euglenophyceae, Myxophyceae and Xanthophyceae were recorded. Total 9 genera of zooplanktons were found with four families namely Rotifera, Cladocera, Copepoda and Ostracoda. Total 56 boats were estimated to be fishing for hilsa between sanctuary and non sanctuary areas of Bangladesh during September to December. Total length of the boats varied between 6.7 and 16.5 m with an average of 13 m.Asian Australas. J. Food Saf. Secur. 2018, 2(2), 79-85